2D thermo elastic behavior of a FG cylinder under thermomechanical loads using a first order temperature theory. (January 2017) - Ghannad, M.; Parhizkar Yaghoobi, M.
Abstract: In this paper, steady state thermo-elastic response of axisymmetric FGM cylinder subjected to pressure and external heat flux in inner surface is presented. Displacement field obeys the kinematics of the first order-shear deformation theory (FSDT) and the first order temperature theory is used. Using energy method, the equilibrium equations and general boundary conditions are derived for a cylinder. It is assumed that properties are varied through the thickness by a volume fraction of inner and outer surface properties, using a power law distribution. Based on the developed analytical solution, extensive numerical results are depicted to provide an insight into the influence of the thermal and mechanical loads, boundary conditions and non-homogeneity indices. Results show that shear stress value has noticeable at boundaries and temperature and displacement fields are strongly dependent on length. Furthermore, it is found that the proposed method is robust and accurate for this kind of problem. Abstract : Thermoelasticity in FGM cylinders subjected to pressure and external heat flux. 2D analysis is based on the energy method and FSDT formulation. First order temperature theory is used to derive Thermal equilibrium equations. It is available for the different thermal and mechanical boundary conditions. The proposed method is robust and no need to study solution convergence.